Mesaconine alleviates doxorubicin-triggered cardiotoxicity and heart failure by activating PINK1-dependent cardiac mitophagy - Zhou, Ji-Chao; Jin, Cai-Cai; Wei, Xiao-Li; Xu, Rui-Bing; Wang, Ruo-Yu; Zhang, Zhi-Meng; Tang, Bo; Yu, Jin-Mei; Yu, Jiao-Jiao; Shang, Shuang; Lv, Xiao-Xi; Hua, Fang; et al. (Frontiers in Pharmacology, 2023)
Aberrant mitophagy has been identified as a driver for energy metabolism disorder in most cardiac pathological processes. However, finding effective targeted agents and uncovering their precise modulatory mechanisms remain unconquered. Fuzi, the lateral roots of Aconitum carmichaelii, shows unique efficacy in reviving Yang for resuscitation, which has been widely used in clinics. As a main cardiotonic component of Fuzi, mesaconine has been proven effective in various cardiomyopathy models. Here, we aimed to define a previously unrevealed cardioprotective mechanism of mesaconine-mediated restoration of obstructive mitophagy. The functional implications of mesaconine were evaluated in doxorubicin (DOX)-induced heart failure models. DOX-treated mice showed characteristic cardiac dysfunction, ectopic myocardial energy disorder, and impaired mitophagy in cardiomyocytes, which could be remarkably reversed by mesaconine. The cardioprotective effect of mesaconine was primarily attributed to its ability to promote the restoration of mitophagy in cardiomyocytes, as evidenced by elevated expression of PINK1, a key mediator of mitophagy induction. Silencing PINK1 or deactivating mitophagy could completely abolish the protective effects of mesaconine. Together, our findings suggest that the cardioprotective effects of mesaconine appear to be dependent on the activation of PINK1-induced mitophagy and that mesaconine may constitute a promising therapeutic agent for the treatment of heart failure.